The molecular mechanisms of Knickkopf and Retroactive proteins in organization and protection of chitin in the newly synthesized insect exoskeleton - Chaudhari, Sujata Suresh (Kansas State University, 2013)
In order to grow and develop, insects must undergo a process of molting, wherein the old cuticle is replaced with a new one. A thin envelope layer has been predicted to act as a physical barrier between molting fluid chitinases and the site of new chitin synthesis ensuring selective protection of newly synthesized chitin. The factors that help the new exoskeleton withstand the deleterious effects of chitinolytic enzymes remain poorly understood. In the current study a mechanistic role for two proteins, Knickkopf (Knk) and Retroactive (Rtv), was explored in organization and protection of the newly synthesized procuticular chitin. Our study demonstrated colocalization of molting fluid chitinases (chitinase-5) with chitin in T. castaneum pharate adult elytral cuticle. Presence of chitinases in the new cuticle, disproved the old theory of the envelope being a protective barrier against chitinases. Confocal and transmission electron microscopic imaging of T. castaneum pharate adult elytral cuticle suggested that Knk protein selectively colocalizes with chitin in the new procuticle, organizes chitin into laminae and protects it from the activity of molting fluid chitinases. Down-regulation of Knk expression resulted in reduction of procuticular chitin, disruption of the laminar architecture of the procuticle and severe molting defects that are ultimately lethal at all stages of insect growth. The presence and activity of Rtv protein ensures the trafficking of Knk into the procuticle. Down regulation of Rtv transcripts showed molting defects and a significant decrease in chitin content similar to those following Knk dsRNA treatment. Confocal microscopic analysis revealed an essential role for Rtv in proper trafficking of Knk from epithelial cells to within the newly synthesized procuticule. Once released into the procuticle, Knk organizes and protects chitin from chitinases. The conservation of Knk and Rtv in all insect species suggests a critical role for these proteins in maintenance and protection of chitin in the insect exoskeleton.
Keywords: Tribolium castaneum; Retroactive; Chitinase; Knickkopf; Chitin synthase; Insect cuticle; Biochemistry (0487); Developmental Biology (0758); Molecular Biology (0307)